2022
DOI: 10.1111/jocd.15182
|View full text |Cite
|
Sign up to set email alerts
|

Pro‐Inflammatory versus Anti‐Inflammatory cytokines in atopic dermatitis patients: A case control study

Abstract: Atopic dermatitis (AD) is a chronic relapsing inflammatory skin disorder with significant morbidity and impairment of life quality. Prevalence is increasing around the world; therefore, intensive research is ongoing to understand the mechanisms of development of AD and offer new treatment options for AD patients. Aims: To investigate the association between Inflammatory (IL-17, TNFα, IFNγ) versus anti-Inflammatory Cytokines (IL-35, TGFβ) in AD patients. Patients and Methods: A case control study included 40 AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
(37 reference statements)
1
5
0
Order By: Relevance
“…Furthermore, we found a negative correlation between IL-35 expression in lesional and nonlesional skin and AD severity. Similar to our results, Kiwan et al observed a negative correlation between IL-35 serum level and the severity of the disease assessed by the SCORAD scale [ 14 ]. Moreover, the expression of IL-35 may be a potentially useful clinical biomarker reflecting the severity of AD.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, we found a negative correlation between IL-35 expression in lesional and nonlesional skin and AD severity. Similar to our results, Kiwan et al observed a negative correlation between IL-35 serum level and the severity of the disease assessed by the SCORAD scale [ 14 ]. Moreover, the expression of IL-35 may be a potentially useful clinical biomarker reflecting the severity of AD.…”
Section: Discussionsupporting
confidence: 92%
“…The results of these studies are conflicting. The first study involving AD infants showed increased serum levels of IL-35 in them [ 13 ], while the other study showed decreased serum levels of IL-35 in AD individuals compared to healthy [ 14 ]. Thus, the role of IL-35 in the pathogenesis of AD remains enigmatic.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing serum IL-17 levels between AD and controls has demonstrated trending elevation in AD relative to controls [10], with other studies finding significant IL-17 elevations and in AD sera [11,12], and some also finding significant correlation with disease severity [13][14][15]. AD skin samples have also been found to have relatively higher IL-17 expression [12,16].…”
Section: Il-17 and Atopic Dermatitis: The Plot Thickensmentioning
confidence: 76%
“…Dysregulated levels of IL-35 are observed in many diseases including asthma, allergic rhinitis, CSU, IBD, psoriasis, cancers, viral diseases, and connective tissue diseases as well as AD; research data suggest that IL-35 may play different roles in different diseases [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. For some diseases, the results of IL-35 concentrations obtained in different studies appear to be contradictory.…”
Section: Discussionmentioning
confidence: 99%
“…However, this proposal has limitations. To date, only a few human studies have been carried out on the serum levels of IL-35 in AD [ 30 , 36 ]. Nevertheless, the results from these studies seem inconsistent.…”
Section: Discussionmentioning
confidence: 99%